JJNS Review Panel (Japan Journal of Nursing Science, 2011)
Background Home-based peritoneal dialysis treatment offers greater autonomy and flexibility. However, it also introduces unique patient safety risks. Despite these risks, there is no validated tool to assess patient safety in home settings. Objectives To develop and validate a scale to assess environmental, behavioral, and procedural safety risks in peritoneal dialysis (PD). Methods This study was conducted with 600 patients across eight hospitals. Item generation was informed by literature review, clinical guidelines, existing instruments, and expert consultation, resulting in an initial 50-item pool. Content validity was established through expert opinions. The final analytic sample was randomly divided into two independent subsamples: exploratory factor analysis was conducted with Sample I (n = 300), and confirmatory factor analysis was conducted with Sample II (n = 300). Internal consistency, test-retest reliability, and convergent and discriminant validity were evaluated. Results The final scale consisted of 42 items across four factors: Safe Dialysis Practices, Infection Prevention and Complication Monitoring, Treatment Follow-up and Safety Preparedness, and Fall Prevention and Safety, explaining 80.5% of the total variance. The CFA results confirmed good model fit (χ 2 /df = 2.487; CFI = 0.968; RMSEA = 0.035). The scale demonstrated excellent internal consistency (α = 0.939) and strong test-retest reliability (ICC = 0.938). Convergent and discriminant validity criteria were satisfied. Conclusion The scale is a valid and reliable instrument for assessing patient safety in peritoneal dialysis. It addresses critical domains aligned with international safety frameworks and can support clinicians in identifying safety risks, guiding interventions, and improving outcomes in home dialysis.